Short-run and Long-run Determinants of Violent and Property Crimes in Malaysia Based on National and State Level Data - Tan, Keat Siang (2011)
This study aims to provide a systematic investigation of the socio-economic causes of crime offences in Malaysia for national and state levels. Two empirical analyses, time series and panel data analysis have been used to examine the interactions between different categories of crime and four explanatory variables namely: police size, unemployment rate, higher education level, and real GDP per capita. The econometric modeling adopted in this study is ARDL bound testing method for time series analysis and PMG estimating technique for panel data analysis, to examine both the long-run and short-run effects of socio-economic determinants on various categories of crime listed in the Malaysian crime index. The main findings of the study can be summarized as follows: First, the results have constantly shown that, for both the national and state level, except for higher education level, all socio-economic variables considered have more significant effect on property crimes than violent crimes in the long-run. However, the effect of higher education level on crime is different because it has more effect on violent crimes than property crimes. All socio-economic variables considered do not affect or is less influential on most categories of the crime in the short-run. Second, the influences of the socio-economic factors on crime at the national and state level are slightly different. At the state level, the socio-economic variables considered have a significant effect on the most categories of property and violent crimes, especially in the long-run. The results are mixed with negative and positive correlation or even insignificant and show up most strongly for property crimes than violent crimes. However, their effects are different at the national level where police size, unemployment rate and higher educational level generally do not affect violent crime rate whether in the short-run or long-run. They do affect the property crime; however, police size and higher education level play a limited influence on this type of crime. Third, real GDP per capita and unemployment rate are the most important factors that influence property and violent crime for both at the national level and at the state level in the long-run. Therefore, our results are consistent with most of empirical studies in the economics of crime which suggests that economic conditions play an important role influencing particularly property crimes